Turkish-Russian relations in light of recent conflicts: Syria, Libya, and Nagorno-Karabakh - Galip Dalay (Stiftung Wissenschaft und Politik (SWP), 2021)
Syria is central to the current shape of Turkey-Russia relations. It offers a model of partnership for both countries in a context where their interests are competitive. However, the Syrian-centric cooperation between Turkey and Russia is also special and is thus unlikely to be replicated elsewhere due to structural constraints and contextual nuances. The limits of the Syrian-style model of cooperation between Ankara and Moscow can be observed in Libya as well as Nagorno-Karabakh. Even though the institutional and elite ownership of Turkey's Western relations has weakened, no similar institutional basis exists in Turkey's relations with Russia. As such, the current Ankara-Moscow axis is to a great extent defined by the personal ties between the countries' leaders and geopolitical imperatives. However, if the current shape of relations endures much longer, these personalised relations will gain structural foundations. A major problem for Turkey in its relations with Russia remains the asymmetry, even if interdependent, in favour of Moscow. Yet, the nature of asymmetry is dynamic and subject to change, as Turkey has engaged in what can be termed dependency reduction on Russia, both geopolitically and structurally (energy-wise). Developments at the broader international level, a new administration in the US, and rising tension between Ukraine and Russia indicate that Turkey would face more constraints and higher costs for its hitherto geopolitical balancing act between the West and Russia. The close relations in recent years between Ankara and Moscow also point to the need for Turkey and the West to redefine the nature of their relations, as the Cold War framework of Turkey-US relations and the accession framework of Turkish-European relations increasingly appear to be ill-suited to the present realities.
Keywords: 320